2020
DOI: 10.1590/1806-9282.66.7.986
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear factor erythroid-2 related factor 2 inhibits human disc nucleus pulpous cells apoptosis induced by excessive hydrogen peroxide

Abstract: SUMMARY OBJECTIVE Nuclear factor erythroid-2 related factor 2 (Nrf2)/ antioxidant response element (ARE) is a novel defensive pathway involved in the oxidative and chemical stress of cells. The aim of the study was to explore the role of Nrf2 on the apoptosis of human disc nucleus pulpous cells induced by hydrogen peroxide (H2O2). METHODS The degeneration model of human intervertebral disc nucleus pulpous cells was established. The expression of Nrf2 was interfered with using sulforaphane (SFN); for that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…With the increase in HO dose, cell viability reduced gradually, and only 40% of NPCs was alive after treated with 500 μM HO. Generally, the concentration of HO caused ~ 50% of cell viability was used to induce apoptosis of NPCs [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the increase in HO dose, cell viability reduced gradually, and only 40% of NPCs was alive after treated with 500 μM HO. Generally, the concentration of HO caused ~ 50% of cell viability was used to induce apoptosis of NPCs [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study showed that the two groups of patients differed mainly in cellular response to chemical stress, extrinsic apoptotic signaling pathway, activation of protein kinase activity, and transcription coactivator activity. Oxidative stress has been confirmed as a significant contributor to IDD, with excessive reactive oxygen species causing cellular oxidation and chemical stress, leading to apoptosis of functional disc cells and hastening degeneration (Lin et al, 2020). Protein kinases are critical regulators of cellular function, governing multiple intracellular signaling pathways to maintain normal physiological cell activity (Kupka et al, 2020;Du et al, 2022).…”
Section: Discussionmentioning
confidence: 99%